Kenaf: a multi-purpose crop for several industrial applications : new insights from the Biokenaf Project - Alexopoulou, Efthimia (Green Energy and Technology, 2013)
Natural plant fibers fibres are being increasingly used in manufacturing industrial products because of their renewable and biodegradable natures. Kenaf is an annual bast fibre crop that can provide fibres for several industrial applications (composites, insulation mats, absorbents, bedding material, etc.) as well as raw material for energy exploitation (solid biofuels). Kenaf: A Multi-Purpose Crop for Several Industrial Applications introduces the physiology and field management of kenaf, agronomy, productivity, harvesting as well as its the industrial and energy uses of this promising non-food crop.   Including recent research collected by the BIOKENAF project, Kenaf: A Multi-Purpose Crop for Several Industrial Applications provides a global picture of state of the art research and developments with Kenaf from Asia, USA and Australia. This thorough introduction if followed up with an assessment of the crops economic viability as well as an the environmental impact assessment of kenaf.   Although not a new crop, Kenaf: A Multi-Purpose Crop for Several Industrial Applications provides a comprehensive introduction to this crop and its developing applications for energy engineers, industry managers, politicians and managers working to develop sustainable energy sources and bio-economies.